2006
DOI: 10.1097/01.aud.0000233891.86809.df
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Potential Benefit of Time-Frequency Gain Manipulation

Abstract: The results indicated that a single-microphone NR system based on time-frequency gain manipulation improved the HINT thresholds of listeners. However, to obtain benefit in speech intelligibility, the detectors used in such a strategy were required to detect an unrealistically high percentage of the speech energy and to perform the gain manipulations on a fast temporal basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
87
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 44 publications
12
87
0
Order By: Relevance
“…In accord with previous work involving sentences and either algorithm processing (Healy et al, 2013) or IBM processing (Anzalone et al, 2006;Wang et al, 2009), gains were greater for HI than for NH listeners and for modulated than for stationary backgrounds. The HI-listener advantage is promising because it indicates that the algorithm and the IBM are effective despite the multitude of limitations imposed by the impaired auditory system.…”
Section: Hi-listener and Babble Advantagessupporting
confidence: 75%
See 2 more Smart Citations
“…In accord with previous work involving sentences and either algorithm processing (Healy et al, 2013) or IBM processing (Anzalone et al, 2006;Wang et al, 2009), gains were greater for HI than for NH listeners and for modulated than for stationary backgrounds. The HI-listener advantage is promising because it indicates that the algorithm and the IBM are effective despite the multitude of limitations imposed by the impaired auditory system.…”
Section: Hi-listener and Babble Advantagessupporting
confidence: 75%
“…As with the algorithm, it was found that the IBM improved recognition of isolated phonemes, thus extending results observed previously for sentences (Anzalone et al, 2006;Brungart et al, 2006;Li and Loizou, 2008;Wang et al, 2008Wang et al, , 2009Cao et al, 2011;Sinex, 2013). This result should not be surprising, given the effectiveness of algorithm processing observed here and the fact that the algorithm aimed to estimate the IBM.…”
Section: Algorithm and Ibm Processingsupporting
confidence: 73%
See 1 more Smart Citation
“…A number of other studies (Roman et al, 2003;Roman and Wang, 2006;Cooke, 2006;Brungart et al, 2006;Anzalone et al, 2006) have shown that speech synthesized from the ideal binary mask is highly intelligible even when extracted from multi-source mixtures (Roman et al, 2003) or in reverberant conditions (Roman and Wang, 2006). Ideal masks that are not binary but take real values have also been found to improve speech intelligibility (Li and Loizou, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, for a time-frequency (T-F) unit, if the signalto-noise ratio (SNR) within the unit is greater than a local criterion (LC), it will be labeled as 1 and otherwise it will be labeled as 0. Previous studies show that IBM separation produces large improvements in human speech intelligibility [3,4,5]. Therefore, one way to approach monaural speech separation is to estimate the IBM.…”
Section: Introductionmentioning
confidence: 99%